Organization activity of director of high school of physical culture - Приходько, І. І.; Стадник, С. О. (Slobozhanskyi Herald of Science and Sport, 2011)
The tasks activity of director of high school of physical culture are considered, which include three basic elements: organizationally-administrative, pedagogical, creatively-innovative. In research these questioning of leaders is utilized 11 high schools of physical culture of Ukraine. It is certain that a morally psychological climate, created in the collective of high school, external and internal factors, influences on efficiency activity of director. The problem sections of activity are set.